A modified variational model for restoring images with multiplicative noise - Del Rosario, Nicole Marie T.; Neri, Marrick C. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2016)
In this research, a modified version of Dong and Zeng's convex variational model is constructed for restoring images with multiplicative noise. First and second order gradient-based methods are developed to solve the proposed model.
Thesis (M.S. Applied Mathematics)--University of the Philippines Diliman
Keywords: Image processing